T- and B-cell immunosuppressive activity of novel α-santonin analogs with humoral and cellular immune response in Balb/c mice12. Issue 1 (28th November 2016) - Dangroo, Nisar A.; Singh, Jasvinder; Gupta, Nidhi; Singh, Shashank; Kaul, Anapurna; Khuroo, Mohmmed A.; Sangwan, Payare L.
Abstract : Herein we report the synthesis of α-santonin analogs, and identification of potent immunosuppressant molecules. In vivo investigation on BALB/c mice revealed that compound4e suppresses both humoral and cellular immunity. Abstract : In continuation of our endeavours to synthesize immunosuppressive agents from α-santonin, we report herein the design and synthesis of a new series of α-santonin derived O-aryl/aliphatic ether, ester and amide analogs and the evaluation of their immunosuppressive activities. The in vitro studies led to several analogs with significant immunosuppressive effects by inhibiting ConA and LPS stimulated T- and B-cell proliferation in a dose dependent manner. The more significant compounds4d, 4e, 4f, 4h, 6a and6b displayed potent inhibitory activity on the mitogen-induced T- and B-cell proliferation in comparison to α-santonin1 . Compound4e displayed stupendous in vitro immunosuppressive effects with ∼80% suppression of B and ∼75% suppression of T lymphocyte proliferation, respectively . The in vivo investigation on BALB/c mice revealed that non-cytotoxic compound4e suppresses both humoral and cellular immunity.